2019
DOI: 10.1111/cen.13981
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 23 levels decline following sleeve gastrectomy

Abstract: The bone-derived protein fibroblast growth factor 23 (FGF23) is a key regulator of phosphate and vitamin D homeostasis. A number of pieces of evidence link both circulating phosphate and FGF23 concentrations with measures of adiposity, cardiovascular risk and mortality. 1-7 Our group 8 and others 1-3 have demonstrated positive associations between circulating FGF23 and body mass index (BMI), fat mass and abdominal circumference in cross-sectional human studies. Furthermore, positive associations between FGF23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(72 reference statements)
0
5
0
Order By: Relevance
“…Normalization of adiponectin in animal models has been associated with preventing cardiac dysfunction ( 35 ) indicating the importance of its restoration to non-obese levels. Adipsin, the other adipokine measured, was higher in the non-surgical comparator-subjects-with-obesity compared to normal-weight subjects though was no different to the surgical patients; adipsin was not shown to change after weight loss following sleeve gastrectomy ( 36 ) indicating that weight loss, but not to normal weight, was ineffective for modulation of this adipokine, as is confirmed here.FGF23 levels were significantly lower in normal-weight subjects compared to surgery and the non-surgical comparator-subjects-with-obesity, an observation that has been reported following sleeve gastrectomy ( 30 ). Whilst FGF23 is recognized to decrease after surgery ( 30 ), that fall was not compared to a normal population and therefore a novel finding of this study is that the fall reported here is not to the level found in subjects with a normal BMI.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Normalization of adiponectin in animal models has been associated with preventing cardiac dysfunction ( 35 ) indicating the importance of its restoration to non-obese levels. Adipsin, the other adipokine measured, was higher in the non-surgical comparator-subjects-with-obesity compared to normal-weight subjects though was no different to the surgical patients; adipsin was not shown to change after weight loss following sleeve gastrectomy ( 36 ) indicating that weight loss, but not to normal weight, was ineffective for modulation of this adipokine, as is confirmed here.FGF23 levels were significantly lower in normal-weight subjects compared to surgery and the non-surgical comparator-subjects-with-obesity, an observation that has been reported following sleeve gastrectomy ( 30 ). Whilst FGF23 is recognized to decrease after surgery ( 30 ), that fall was not compared to a normal population and therefore a novel finding of this study is that the fall reported here is not to the level found in subjects with a normal BMI.…”
Section: Discussionmentioning
confidence: 54%
“…Adipsin, the other adipokine measured, was higher in the non-surgical comparator-subjects-with-obesity compared to normal-weight subjects though was no different to the surgical patients; adipsin was not shown to change after weight loss following sleeve gastrectomy ( 36 ) indicating that weight loss, but not to normal weight, was ineffective for modulation of this adipokine, as is confirmed here.FGF23 levels were significantly lower in normal-weight subjects compared to surgery and the non-surgical comparator-subjects-with-obesity, an observation that has been reported following sleeve gastrectomy ( 30 ). Whilst FGF23 is recognized to decrease after surgery ( 30 ), that fall was not compared to a normal population and therefore a novel finding of this study is that the fall reported here is not to the level found in subjects with a normal BMI. This is perhaps not surprising as FGF23 has been associated with insulin resistance and inflammation ( 12 ) and, whilst there was a marked decrease in body weight after surgery that would be associated with a reduction in both insulin resistance and inflammation, these patients still had a significant weight difference compared to normal-weight subjects.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, regulation of renal α-klotho by caloric intake could influence FGF23 synthesis and secretion. Studies in humans also support the role of reducing caloric intake on FGF23, e.g., a decrease in circulating FGF23 concentrations has been reported in patients subjected to bariatric surgery [52].…”
Section: Fgf23mentioning
confidence: 77%
“…PTH may also be a candidate factor for this connection because PTH levels are elevated in obese subjects 28 , 29 and there is evidence to show that PTH is a positive regulator for FGF23 12 , 13 . However, Billington et al recently reported that FGF23 concentrations decreased after sleeve gastrectomy independent of changes in adiposity, PTH, and leptin levels 30 , which suggests an additional factor affecting FGF23 concentrations in humans. Based on accumulating evidence showing a relationship between insulin and FGF23 levels in humans 17 , 18 , insulin signaling has been implicated in the regulation of FGF23.…”
Section: Discussionmentioning
confidence: 99%